2004
DOI: 10.1017/s0031182004005967
|View full text |Cite
|
Sign up to set email alerts
|

The global importance of ticks

Abstract: Ticks and tick-borne diseases affect animal and human health worldwide and are the cause of significant economic losses. Approximately 10% of the currently known 867 tick species act as vectors of a broad range of pathogens of domestic animals and humans and are also responsible for damage directly due to their feeding behaviour. The most important tick species and the effects they cause are listed. The impact on the global economy is considered to be high and although some estimates are given, there is a lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1,112
0
27

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,611 publications
(1,144 citation statements)
references
References 31 publications
5
1,112
0
27
Order By: Relevance
“…During the last two decades, a growing interest in tick-borne diseases from veterinary, medical, and public health perspectives has emerged (Jongejan and Uilenberg, 2004). The worldwide prevalence of these diseases is steadily rising, challenging how we approach diagnosis, treatment and preventative control measures, and underlining the importance of the One Health concept (DantasTorres et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, a growing interest in tick-borne diseases from veterinary, medical, and public health perspectives has emerged (Jongejan and Uilenberg, 2004). The worldwide prevalence of these diseases is steadily rising, challenging how we approach diagnosis, treatment and preventative control measures, and underlining the importance of the One Health concept (DantasTorres et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Globally, ticks are considered the most important external parasites of livestock, and they, and the diseases they transmit, represent a severe constraint to successful stock farming in many countries (Jongejan and Uilenberg 2004). Their impact is usually more severe in developing, resource-limited countries than in the developed world (De Castro 1997).…”
Section: Introductionmentioning
confidence: 99%
“…and Ixodes spp. (Uilenberg, 1995;De Waal et al, 2000;Jongejan and Uilenberg, 2004;Kocan et al, 2004). Tick transmissibility of Anaplasma is complex and ranges from very efficient transmission to non-transmission related to both Anaplasma strains as well as species of tick (Ueti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Anaplasmosis has been reported in different regions of Morocco (Verhulst et al, 1983;Sahibi et al, 1998b), but it has a perceived lower incidence compared with theileriosis and babesiosis. Although, severe economic losses have been reported due to anaplasmosis outbreaks in several parts of the world (Herrero et al, 1998;Kocan et al, 2000Kocan et al, , 2004Grisi et al, 2002;Jongejan and Uilenberg, 2004), no specific disease outbreak of A. marginale in cattle has been reported in Morocco and the only epidemiological studies of anaplasmosis reported previously were conducted more than a decade ago (Sahibi et al, 1998b).…”
Section: Introductionmentioning
confidence: 99%